2012
DOI: 10.1038/ja.2012.89
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of Pheroid vesicles containing antibiotics against Plasmodium falciparum

Abstract: The macrolide antibiotics, erythromycin and azithromycin, have been studied for their potential antimalarial activity, but only modest activity has been demonstrated. In this study, we investigated the enhancement of the efficacy of these antibiotics in combination with a patented lipid-based drug delivery system, Pheroid technology. A chloroquine resistant strain of Plasmodium falciparum (RSA11) was incubated with the formulations for a prolonged incubation time (144 h). Drug efficacy assays were conducted by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 47 publications
(64 reference statements)
0
7
0
Order By: Relevance
“…Pheroid technologyV R is a unique sub-micron-to nano-formulation that can entrap, transport, and deliver the active ingredient in an effective way in humans and plants. The Pheroid formulation is a stable structure that can be manipulated and controlled to specifically enhance the absorption of various active ingredients which can result in enhanced metabolic activity (Du Plessis et al 2012;2014;). The Pheroid system is composed of an organic carbon backbone and fatty acids that result in vesicles and sponges in the size of nano to micron, that can be manipulated to entrap hydrophilic, hydrophobic, or amphiphilic compounds for transport across numerous biological membranes (Grobler 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Pheroid technologyV R is a unique sub-micron-to nano-formulation that can entrap, transport, and deliver the active ingredient in an effective way in humans and plants. The Pheroid formulation is a stable structure that can be manipulated and controlled to specifically enhance the absorption of various active ingredients which can result in enhanced metabolic activity (Du Plessis et al 2012;2014;). The Pheroid system is composed of an organic carbon backbone and fatty acids that result in vesicles and sponges in the size of nano to micron, that can be manipulated to entrap hydrophilic, hydrophobic, or amphiphilic compounds for transport across numerous biological membranes (Grobler 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A Pheroid delivery system has been shown to increase the in vitro antimalarial activities of azithromycin, mefloquine, and quinine significantly (20,21). Entrapment of artemisone in Pheroid vesicles also has been shown to enhance blood artemisone concentrations in mice (22) and primates (23).…”
mentioning
confidence: 99%
“…MQ was incorporated by first dissolving the drug in dl‐α‐tocopherol and then adding the appropriate amount of nitrous oxide PBS to form a Pheroid‐drug complex. This strategy has proved successful in previous studies with various antimalarial drugs …”
Section: Resultsmentioning
confidence: 99%
“…These vesicles have proved successful in increasing the bioavailability of the poorly soluble prototype antimalarial drug, artemisone, but not artemiside . We have previously shown that Pheroid vesicles are stable and have an entrapment efficiency of 67% for MQ, and proved effective in increasing the in‐vitro antimalarial efficacy of chloroquine, erythromycin, azithromycin, doxycycline and tetracycline …”
Section: Introductionmentioning
confidence: 99%